Acculturative stress, loneliness, smartphone addiction, L2 emotions, and creativity among international students in China: a structural equation model - Gao, Jian; Xu, Dan; Romano, Daniela; Hu, Xuhui (Frontiers in Psychiatry, 2025)
IntroductionInternational students in China often face psychological challenges such as acculturative stress, loneliness, and problematic smartphone use, which may affect their second language (L2) learning emotions and creativity. Although these factors have been studied individually, their interrelationships remain unclear.MethodsData were collected from 213 international students studying in China using validated instruments: the Acculturative Stress Scale for International Students (ASSIS), UCLA Loneliness Scale, Smartphone Addiction Scale Short Version (SAS-SV), Foreign Language Enjoyment and Classroom Anxiety Scale (FLE & FLCA), and the Inventory of Creative Activities and Achievements (ICAA). Structural equation modeling (SEM) was employed to assess the hypothesized model and test both direct and indirect relationships among the constructs.ResultsAcculturative stress significantly predicted smartphone addiction directly (β = 0.372, p < .001) and indirectly via loneliness (β = 0.169, p < .005). It also influenced FLCA through a chain mediation of loneliness and smartphone addiction (β = 0.135, p < .005). In terms of creativity, both acculturative stress (β = 0.300, p < .001) and FLE (β = 0.310, p < .001) positively predicted creative activities, which in turn strongly predicted creative achievement (β = 0.700, p < .001). FLCA was also positively related to creative achievement (β = 0.118, p = .016).DiscussionThese findings support the Dual Pathway to Creativity Model and suggest that long-term moods (e.g., acculturative stress) and situational emotions (e.g., FLE and FLCA) may differentially affect creativity, aligning with the Hierarchical Model of Affect, Mood, and Emotion, advancing the understanding of international students' cross-cultural adaptation in the digital age.